Increasing inclusiveness for women, youth and seniors in Canada - Barker, Andrew (OECD Publishing, 2018)
Women, youth and seniors face barriers to economic inclusion in Canada, with considerable scope to improve their labour market outcomes. There has been no progress in shrinking the gender employment gap since 2009, and women, particularly mothers, continue to earn significantly less than men, in part due to a large gap in unpaid childcare responsibilities. Outside the province of Québec, low (but increasing) rates of government support for childcare should be expanded considerably, as should fathers' low take-up of parental leave. Skills development should be prioritised to arrest declining skills among youth and weak wage growth among young males with low educational attainment. Fragmented labour market information needs to be consolidated to address wage penalties associated with the widespread prevalence of qualifications mismatch. Growth in old-age poverty should be tackled through further increases in basic pension payments over time. Linking changes in the age of eligibility for public pensions to life expectancy would boost growth by increasing employment of older Canadians still willing and able to work. For all three groups, well-targeted expansions of in-work tax benefits and active labour market spending have the potential to increase employment
Keywords: Economics; Canada